'Only twice a year': a qualitative exploration of 6-month antiretroviral treatment refills in adherence clubs for people living with HIV in Khayelitsha, South Africa. Issue 7 (8th July 2020) - Keene, Claire Marriott; Zokufa, Nompumelelo; Venables, Emilie C; Wilkinson, Lynne; Hoffman, Risa; Cassidy, Tali; Snyman, Leigh; Grimsrud, Anna; Voget, Jacqueline; von der Heyden, Erin; Zide-Ndzungu, Siphokazi; Bhardwaj, Vinayak; et al.
Abstract : Objective: Longer intervals between routine clinic visits and medication refills are part of patient-centred, differentiated service delivery (DSD). They have been shown to improve patient outcomes as well as optimise health services—vital as 'universal test-and-treat' targets increase numbers of HIV patients on antiretroviral treatment (ART). This qualitative study explored patient, healthcare worker and key informant experiences and perceptions of extending ART refills to 6 months in adherence clubs in Khayelitsha, South Africa. Design and setting: In-depth interviews were conducted in isiXhosa with purposively selected patients and in English with healthcare workers and key informants. All transcripts were audio-recorded, transcribed and translated to English, manually coded and thematically analysed. The participants had been involved in a randomised controlled trial evaluating multi-month ART dispensing in adherence clubs, comparing 6-month and 2-month refills. Participants: Twenty-three patients, seven healthcare workers and six key informants. Results: Patients found that 6-month refills increased convenience and reduced unintended disclosure. Contrary to key informant concerns about patients' responsibility to manage larger quantities of ART, patients receiving 6-month refills were highly motivated and did not face challenges transporting, storing or adhering to treatment. All participant groups suggested that strict eligibility criteria were necessary for patients to realise the benefits of extended dispensing intervals. Six-month refills were felt to increase health system efficiency, but there were concerns about whether the existing drug supply system could adapt to 6-month refills on a larger scale. Conclusions: Patients, healthcare workers and key informants found 6-month refills within adherence clubs acceptable and beneficial, but concerns were raised about the reliability of the supply chain to manage extended multi-month dispensing. Stepwise, slow expansion could avoid overstressing supply and allow time for the health system to adapt, permitting 6-month ART refills to enhance current DSD options to be more efficient and patient-centred within current health system constraints.